2017
DOI: 10.1021/acsearthspacechem.6b00011
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Induced Synthesis of Formamide in Condensed Mixtures of Carbon Monoxide and Ammonia

Abstract: The formation of the prebiotically relevant molecule formamide under electron exposure of ammonia and carbon monoxide was studied at cryogenic temperatures of 30−35 K. Postirradiation thermal desorption spectroscopy was used to study the energy dependence of the reaction. A resonant process centered around ∼9 eV and a threshold type increase of the yield above ∼12 eV were observed. On the basis of the absence of particular side products such as urea and ethanediamide and supported by quantum chemical calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 38 publications
2
45
4
Order By: Relevance
“…In ideal cases, the products can even incorporate all atoms of the initial reactants [16]. As prototypical examples, the syntheses of ethylamine (CH 2 H 5 NH 2 ) from ethylene (C 2 H 4 ) and ammonia (NH 3 ) [17], ethanol (C 2 H 5 OH) from ethylene (C 2 H 4 ) and water (H 2 O) [18], as well as formamide (H 2 NCHO) from carbon monoxide (CO) and ammonia (NH 3 ) [19] have been observed under low-energy electron irradiation in cryogenic condensed ices cona e-mail: swiderek@uni-bremen.de (corresponding author) taining the starting compounds. It was proposed in all three cases that electron ionization (EI) of one of the reactants creates an attractive force between adjacent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In ideal cases, the products can even incorporate all atoms of the initial reactants [16]. As prototypical examples, the syntheses of ethylamine (CH 2 H 5 NH 2 ) from ethylene (C 2 H 4 ) and ammonia (NH 3 ) [17], ethanol (C 2 H 5 OH) from ethylene (C 2 H 4 ) and water (H 2 O) [18], as well as formamide (H 2 NCHO) from carbon monoxide (CO) and ammonia (NH 3 ) [19] have been observed under low-energy electron irradiation in cryogenic condensed ices cona e-mail: swiderek@uni-bremen.de (corresponding author) taining the starting compounds. It was proposed in all three cases that electron ionization (EI) of one of the reactants creates an attractive force between adjacent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The production of formamide present in mixed multilayer films of CO and NH 3 . The resonance like feature (red line) between 6 and 12 eV is characteristic of the synthesis of formamide by reactants prepared in a DEA process, Bredehöft et al [71].…”
Section: Electron Energy [Ev]mentioning
confidence: 98%
“…The ice was prepared with a mixing ratio of 1:8 and thickness corresponding to 12-18 monolayers and an electron exposure of 200 µC/cm 2 . Formamide is readily formed and the resonance like feature between 6 and 12 eV is characteristic of the synthesis by reactants prepared in a dissociative electron attachment process [71]. Similar experiments have shown that as many as 15 products can be formed by electron irradiation of pure methanol ices [72] including ethylene glycol and methyl formate whilst formamide HCONH 2 is formed in irradiation of binary mixtures of ammonia and methanol ice and the simplest amino acid glycine from irradiation of a methylamine and carbon dioxide ice [73].…”
Section: Possibility Of Electron Induced Surface Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…cleavage of molecular bonds as well as possible molecular rearrangement and formation of new molecular bonds) of the involved molecular species. For example, the electron-induced synthesis of FA in an icy mixture of CO and was proposed via electron attachment as well as electron ionization [ 12 ]. Moreover, FA and its analogues, containing the amide bond, a key biochemical structure, serve as model systems to understand the role of low-energy electrons in radiation damage to the cellular compounds [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%